2011
DOI: 10.1016/j.ijimpeng.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative numerical studies of projectile impacts on plain and steel-fibre reinforced concrete

Abstract: The enhanced energy absorption characteristics of fibre-reinforced concrete, compared to plain concrete, has in experimentally studies been shown to improve the projectile resistance and motivate its increased usage in protective structures. However, the high cost of undertaking experiments and the high parameter variation and dependency of the experimental setups and results, respectively, make it difficult to draw generic conclusions of how the addition and increased amount of fibres affects the local damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…7 and 10). Similar results were obtained by numerical simulation of projectile with and without spike impacting concrete target with different volumes of fiber reinforcement [13].…”
Section: Comparisonsupporting
confidence: 81%
“…7 and 10). Similar results were obtained by numerical simulation of projectile with and without spike impacting concrete target with different volumes of fiber reinforcement [13].…”
Section: Comparisonsupporting
confidence: 81%
“…The studies of Nyström et al [5] showed that the crack propagation and the penetration depth resistances of the fiber-reinforced concrete against projectile were improved and so they could be efficiently used in the protective structures.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The studies of Nyström et al [5] showed that the crack propagation and the penetration depth resistances of the fiber-reinforced concrete against projectile were improved and so they could be efficiently used in the protective structures. A novel type of reinforcement for polymers, composites and also concrete is the carbon nanotube (CNT) [6], which is a very high strength material at the atomic scale.…”
mentioning
confidence: 99%
“…The inclusion of fibres to cementitious concrete or matrix results in improved post-cracking behaviour. Hence the main difference between material models used for plain concrete and steel fibre reinforced composite material is the failure description on tension [28][29][30][31]. Due to the enhanced ductility of fibre reinforced materials, the crack control ability and energy absorption capacity Table 2 Distribution of gauge points in the FE model.…”
Section: Modifications Made To Rht Modelmentioning
confidence: 99%